Co-digestion of poultry manure and residues from enzymatic saccharification and dewatering of sugar beet pulp. (December 2016) - Borowski, Sebastian; Kucner, Marcin; Czyżowska, Agata; Berłowska, Joanna
Abstract: This study investigates the co-digestion of poultry manure (PM) with sugar beet pulp residues (SBPR) obtained from saccharification and dewatering of sugar beet pulp. The laboratory-scale experiments were conducted under batch and semi-continuous conditions at mesophilic temperatures (35 °C). Batch tests gave specific biogas and methane yields of 590 dm 3 /kgVSfed and 423 dm 3 CH4 /kgVSfed, respectively for SBPR, whereas the corresponding values for PM were 434 dm 3 /kgVSfed and 300 dm 3 CH4 /kgVSfed . The co-digestion of PM with SBPR was found to increase biogas and methane yields compared to the manure alone. In semi-continuous reactor experiments, the highest methane yield of 346 dm 3 CH4 /kgVSfed was achieved for the mixture containing poultry manure with 50% SBPR (weight basis) and a solids retention time (SRT) of 20 days. However, when poultry manure was digested as a sole feedstock, the biogas production was inhibited by ammonia, whereas the co-digestion of PM with 25% SBPR was slightly affected by volatile fatty acids, which concentrations exceeded 4000 g/m 3 . Highlights: Co-digestion of sugar beet pulp residues (SBPR) with poultry manure (PM) was studied. PM co-digested with 50% SBPR gave the highest methane production of 346 dm 3 /kgVS. Ammonia concentration greater than 200 g/m 3 was inhibitory for PM mono-digestion. Co-digestion of PM with 25% SBPR was slightly affected by volatile fatty acids.